Patient's Perception of Nasal Function and Cosmesis After Maxillomandibular Advancement for Obstructive Sleep Apnea - Abdelwahab, Mohamed; Huang, Allen; Chou, Courtney; Fleury, Thomaz; Riley, Robert; Most, Sam; Liu, Stanley (Archives of facial plastic surgery, 2023)
Maxillomandibular advancement (MMA) remains one of the most effective surgeries for the treatment of obstructive sleep apnea (OSA), but it can be difficult to manage nasal and midfacial esthetics for patients requiring significant maxillary advancement. To evaluate changes in the Standardized Cosmesis and Health Nasal Outcomes Survey (SCHNOS) after the modified MMA approach. This prospective study was conducted on subjects undergoing MMA at a tertiary referral center from September 2020 to August 2021. Nasal function, cosmesis, and sleepiness were assessed perioperatively with the SCHNOS, visual analog scale for nasal function and cosmesis, and Epworth sleepiness scale (ESS). Objective polysomnography data were also investigated. Thirty-one subjects met inclusion criteria. After MMA, SCHNOS-O (obstruction domain) improved from 44.38 ± 26.21 to 19.03 ± -4.75 ( < 0.001). The SCHNOS-C (cosmesis domain) improved significantly from 13.95 ± 19.32 to 5.27 ± 8.93 ( = 0.029). Specific items evaluating self-esteem, nasal straightness, and symmetry showed significant improvement ( = 0.006, 0.025, 0.044). The ESS also improved from 9.41 ± 6.11 to 3.26 ± 3.03 ( < 0.001), and it correlated with nasal obstruction scores. In this study, patients' perception of nasal obstruction and appearance improved after applying the nasal modifications to MMA described for OSA.